Education In Increasing FE Tablet Consumption In Kualuh Hilir District In 2023 - Christo Christo; Citra Dewi Fitri (Lembaga Pengembangan Kinerja Dosen, 2023)
In pregnant women, iron plays an important role in fetal growth. This study aims to determine the relationship between husband's knowledge and support and compliance with pregnant women consuming Fe tablets at the Kampung Mesjid Community Health Center, Kec. Kualuh Hilir in 2023. This type of research is an analytical survey with a cross-sectional research design. The number of samples used was 40 people obtained using total sampling techniques. The data analysis technique uses chi square. Based on the chi square test results, there is a relationship between knowledge and compliance with pregnant women consuming Fe tablets with a P value = 0.002 < 0.05, there is a relationship between husband's support and compliance with pregnant women consuming Fe tablets with a P value = 0.008 < 0.05. It is recommended that pregnant women increase their compliance in consuming Fe tablets during their pregnancy to maintain the health of themselves and their womb.